TRANFORMASI ESTETIKA LUKIS KACA KONTEMPORER INDONESIA: DARI TRADISI KE EKSPRESI MODERN (1980-SEKARANG) - Clarisa Cakrajaya; Livia Setiawan; Novia Viviana Sudjianto; Rachel Caliesta Zefanya; Breitling Andrea Gunawan (Lembaga Berugak Baca, 2025)
Glass painting is a tradition of fine art that is painted and colored from the back of the glass. Painters choose glass as a medium because it can display detailed images. Glass painting experiences many difficulties and obstacles to maintaining its tradition based on the passage of time, glass painting in Indonesia has undergone a transformation in aesthetics through concepts and manufacturing processes. The purpose of this study is to understand the development of glass painting in the archipelago and actions in preserving it in the era of contemporary art and the results of acculturation with techniques and concepts in painting on glass. This type of research is quantitative research. The research method used in this study is to collect and analyze data. The results of this study show a combination of culture and techniques that can elevate unique artistic values.